Traditional Indonesian Games as a Medium for Enhancing Gross and Fine Motor Skills in Preschool Children: A Systematic Literature Review - Ari Gana Yulianto; Yudha Munajat Saputra; Teguh Satria; Aris Risyanto (Journal of Physical Education Health and Sport, 2025)
Early motor skill development is essential for socioemotional development, cognitive development, and physical preparedness. However, children’s chances for sufficient motor stimulation have decreased in Indonesia due to shifting activity patterns and constrained play areas. A culturally grounded educational alternative that gives organic and comprehensive motor experiences is traditional Indonesian games. This study aims to summarize evidence on the potential of traditional games as inclusive and sustainable methods to support Indonesian children’s development. This study used a Systematic Literature Review (SLR) in accordance with PRISMA 2020, looking for articles published between 2015 and 2025 using Scopus, Web of Science, ScienceDirect, and Google Scholar. Ten of the 1,222 records that were found satisfied the requirements for inclusion following screening and quality evaluation using the JBI checklist. Research demonstrates that games like engklek, gobak sodor, bentengan, congklak, and bekel regularly improve hand-eye coordination, muscular strength, agility, balance, and coordination. Significant improvements were seen in both the gross and fine motor domains throughout interventions spanning 4–8 weeks with two–three weekly sessions. Additionally, traditional games promote sensorimotor learning, social interaction, and intrinsic drive. Traditional games are an efficient, affordable, and culturally appropriate way to assist preschool motor development, despite the fact that many studies used quasi-experimental techniques with small sample sizes. These findings offer compelling evidence for its incorporation into national curricular efforts and early childhood education practices.